Wendy Wasserstein - Dolan, Jill, 1957- (Michigan modern dramatists., 2017)
Playwright Wendy Wasserstein (1950-2006), author of The Heidi Chronicles, wrote topical, humorous plays addressing relationships among women and their families, taking the temperature of social moments from the 1960s onward to debate women's rightful place in their professional and personal lives. The playwright's popular plays continue to be produced on Broadway and in regional theaters around the country and the world. Wasserstein's emergence as a popular dramatist in the 1970s paralleled the emergence of the second-wave feminist movement in the United States, a cultural context reflected in the themes of her plays. Yet while some of her comedies and witty dramas were wildly successful, packing theaters and winning awards, feminists of the era often felt that the plays did not go far enough. Wendy Wasserstein provides a critical introduction and a feminist reappraisal of the significant plays of one of the most famous contemporary American women playwrights. Following a biographical introduction, chapters address each of her important plays, situating Wasserstein's work in the history of the US feminist movement and in a historical moment in which women artists continue to struggle for recognition.